Pedagogical Conditions Of Training Professional Education Teachers - Akhadova Gulnoza (Genius Journals, 2024)
This article discusses the pedagogical conditions for training teachers of professional education. The tasks, foundations and signs of pedagogical conditions for the implementation of the pedagogical strategy of training teachers of professional education are revealed.
Keywords: Pedagogical Conditions; Educational Process Subjects; Pedagogical System